Risk Factors associated with Intrauterine Fetal Death at Birat Medical College Teaching Hospital - Mahato, Raj Deb; Singh, Ajit; Shrestha, Binish Man; Joshi, Manisha; Singh, Sujeet; Singh, Ajit; Pradhan, Tarun (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Intrauterine fetal death is a tragic event, and despite efforts to reduce its incidence, it remains challenging to do so. Intrauterine fetal death is an important indicator of the maternal and perinatal health of a given population. This study aims to identify the maternal and fetal factors associated with intrauterine fetal death.Material and Methods: This is a descriptive cross-sectional study conducted in Obstetrics ward of Birat Medical College Teaching Hospital from 1st July 2021 to 31st August 2022. All pregnant women with ultrasound confirmed intrauterine fetal death after 28 or more weeks gestation who were admitted to the Obstetrics ward of Birat Medical College Teaching Hospital in the study period were enrolled in the study.Results: There were 4562 antenatal admissions and 3852 deliveries in the study period. Of these, 35 pregnant women were admitted with intrauterine fetal death. The intrauterine fetal death rate was 11 per 1000 deliveries in our institution. The mean age of women at presentation was 25.94±4.82 years, and 85.7% of pregnant women between the ages of 20-35 years. Of the study participants, 34.3% were Janajati and 82.9 % were Hindu. Out of 35 pregnant women, 37.1% had not received formal education, and all of them were housewives by occupation. Only one patient was smoker, and none of them were alcoholic. Among the 35 pregnant women, 40 % were preterm, 57.1% were term, and 2.9% were post-term. The majority (60%) of them were multigravida. Hypertensive disorder in pregnancy was the most common identified risk factor in 25.7% of pregnant women, and in 37.1 % of cases, causes were not identified. Out of the 35 pregnant women, 34 underwent vaginal delivery, while one underwent a caesarean section for placenta previa.Conclusion: Most of the pregnant women with intrauterine fetal death were illiterate housewives. The most commonly identified risk factor in this study was hypertensive disorder in pregnancy, which is preventable by regular antenatal care and timely intervention. Therefore, we should emphasize the importance of regular antenatal care for early detection and treatment of hypertension and other risk factors.